Conceptual Feasibility of a Portable Containerized and Decentralized Wastewater Treatment System for Rural Regions: A Case Study in Palestine - Mahmoud Sallam; Amal Yaseen; Leena Refai; Amjad El-Qanni (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The necessary implementation of decentralized wastewater treatment systems in densely populated rural regions is a viable alternative to constructing a large centralized system. Therefore, this study aims to assess the conceptual feasibility of implementing a portable containerized and decentralized wastewater treatment system as a case study in Palestine that can help in treating wastewater in rural areas efficiently generated by up to 4,000 individuals. The conceptually proposed system is comprised of two stages. The initial stage includes a standalone primary sedimentation tank located outside the container. The subsequent stage consists of a container housing all the equipment utilized in the treatment process beginning with aeration, followed by secondary sedimentation, and ending with filtration and chlorination. Although the system is designed as a single container, in practice, it will consist of two containers with identical units. The second container will ensure continuous operation mode in case of maintenance in the first container. An initial cost evaluation was conducted, and the projected cost for one container is roughly $9,800, which is reasonable. Indeed, adopting this proposed system would result in a significant cost-saving of approximately 40 million dollars compared to the current west wastewater treatment plant in Nablus. Additional research can be undertaken to explore the running cost and the level of efficacy attained